Indwelling catheter associated urinary tract infection - Poudel, CM; Baniya, G; Pokhrel, BM (Journal of Institute of Medicine Nepal, 2009)
Background: The objective of the study is determined the microbiological profile and the resistance pattern of the strains causing Foley's Catheter Associated Urinary Tract Infection. Materials and methods: It was a prospective study conducted in catheterized patients admitted in medical ward in Tribhuvan University Teaching Hospital (TUTH). A total of 100 adult patients above 16 years in whom an indwelling Foley‘s catheter inserted for short to intermediate term purpose were taken in the study. Quantitative culture of urine sample was done at the time of catheterization and was repeated on 3rd-5th day, 7th day, 10th day, 14th day and then every weekly until catheter removal or patient develops bacteriuria or until discharge of the patient at Microbiology Department Laboratory TUTH. Three ml of urine specimen were obtained aseptically and were sent to laboratory within 1 hour of collection. Antibiotic sensitivity test was done by Disk-Diffusion Technique. Results: The most common organism causing CAUTI was found to be E.Coli in 40% of cases, followed by Klebsiella, Enterococcus, Streptococcus faecalis, Pseudomonas, Staphylococcus aureus, Acinetobacter sp.and multiple bacteria. Ninety percent of E. coli isolates tested were found to be resistant to Amphicillin, Ciprofloxacin and Cephalexin, 86% were resistant to Cotrimoxazole, Coamoxiclav, 68% to Gentamycin, 41% to Ceftazidime, 36.4% to Amikacin, 22% to Nitrofurantoin, 9% to Piperacillin and non of them were resistant to Imepenem. Conclusion: E. coli was the most common organism causing CAUTI. E. coli was found to be resistant to most of the antibiotics. The organism was not resistent to Imepenem. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 3-7